LA INCIDENCIA DE LA TRIQUINOSIS EN GUADALAJARA JAL REVELADA POR EL ESTUDIO POSTMORTEM DE DIAFRAGMAS HUMANAS - RUIZ SANCHEZ; OROZCO GARCIA (Instituto de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1946)
The portions of the acoustic labyrinth, in which the mammalian cochlea is probably represented by the pars basilaris, the different fibers which form the terminal nerves and the nerve endings in the cristae acusticae and maculae acusticae were studied in
REV MEX MED
Keywords: INCIDENCIA, TRIQUINOSIS,GUADALAJARA, ESTUDIO, POSTMORTEM, DIAFRAGMAS, HUMANAS; CIENCIAS MEDICAS; MEDICINA FORENSE